Endogenous Endophthalmitis: Recommendation for Empiric Dual Antibacterial and Antifungal Therapy. (May 2021) - Amarasekera, Sohani; Doss, Mallika; Banaee, Touka; Kowalski, Regis P.; Eller, Andrew W.
Purpose: This work compares clinical presentation and course of bacterial and fungal causes of endogenous endophthalmitis (EE). Methods: A single-institutional study of consecutive patients diagnosed with EE was conducted at the University of Pittsburgh Medical Center between September 2015 and September 2018. Exclusion criteria included history of ocular trauma, intraocular surgery or injection 6 months before presentation, or primary external ocular infection. Data included demographics, medical and ocular history, clinical examination, culture data, therapeutic interventions, final corrected visual acuity (VA), and mortality. Results: Thirty-six eyes of 26 patients were diagnosed with EE during a 3-year period. Median age at diagnosis was 55.5 years (range, 19-86 years). Based on ocular and systemic cultures, 19 patients had bacterial EE and 6 patients had fungal EE; findings from all cultures remained negative in 1 patient. All patients had risk factors for EE. Presenting VA, subjective symptom report, and objective measures of intraocular inflammation were similar between bacterial and fungal causes. Overall, EE presented indolently and was initially misdiagnosed in 19% of cases. Complications including final VA less than 20/200, retinal detachment, enucleation, or death within 6 months of diagnosis were equivalent between bacterial and fungal cases. Conclusions: The presentation of EE is remarkably different from that of exogenous endophthalmitis. Without a high index of suspicion, the indolent presentation of EE may lead to misdiagnosis. No clinical features reliably differentiated bacterial and fungal sources. This highlights the importance of considering empiric therapy for antibacterial and antifungal coverage on initial presentation.